Feeding foliar nano-selenium biofortified panax notoginseng could reduce the occurrence of glycolipid metabolism disorder in mice caused by high-fat diets - Dong, Qinyong; Yan, Sen; Li, Dong; Zhou, Chunran; Tian, Sinuo; Wang, Yu; Miao, Peijuan; Zhu, Wentao; Zhu, Shusheng; Pan, Canping (Frontiers in Nutrition, 2022)
Nano-selenium (nano-Se) has been extensively explored as a biostimulant for improving the quality of grain crops. However, there are few reports about the effect on the medicinal components in Chinese herbal medicine Panax notoginseng (PN) cultured with nano-Se and glycolipid metabolism in mice. In this study, the correlations in saponins in PN and biochemical parameters, gene expression, and gut microbiota related to glycolipid metabolism in mice were examined by the target determination and 16S rRNA gene sequence analysis. Compared with the control groups, foliar spraying of nano-Se increased saponins contents (Rb2, Rb3, Rc, F2, Rb2, and Rf) in the roots of Panax notoginseng, the content of Rb2 increased by 3.9 times particularly. Interestingly, animal studies indicated that taking selenium-rich Panax notoginseng (SePN) can further ameliorate liver antioxidation (SOD, MDA, and GSH) and enzyme activities involved in glycolipid metabolism (ATGL and PFK). It also relieved inflammation and regulated the expression of genes (MCAD, PPAY-α, and PCSK9) related to fatty acid oxidation. The abundance ratio of Firmicutes/Bacteroides and beneficial bacteria abundance (Bifidobacterium, Butyricimonas, and Parasutterella) in gut microbiota were improved relative to the control. In summary, the application of nano-Se on PN may effectively raise the content of Panax notoginseng saponins (PNS) and immensely lower the risk of metabolic disorders of glycolipids.